2004
DOI: 10.1016/j.pain.2004.09.026
|View full text |Cite
|
Sign up to set email alerts
|

The effectiveness of physiotherapy and manipulation in patients with tension-type headache: a systematic review

Abstract: The study design is a systematic review of randomised clinical trials (RCTs). The objectives of the present study are to assess the effectiveness of physiotherapy and (spinal) manipulation in patients with tension-type headache (TTH). No systematic review exists concerning the effectiveness of physiotherapy and (spinal) manipulation primarily focussing on TTH. Literature was searched using a computerised search of MEDLINE, EMBASE and the Cochrane library. Only RCTs including physiotherapy and/or (spinal) manip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
70
1
4

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 99 publications
(76 citation statements)
references
References 27 publications
1
70
1
4
Order By: Relevance
“…This finding further supports systematic reviews that have reported inconsistent and inconclusive effectiveness of physical treatments in tension-type headache aimed at mobilization. 14, 24,26 Considering these results and reported risks of cervical high-velocity thrust mobilization techniques, 1 clinicians should reconsider the use of these techniques in participants with CTTH.…”
Section: Discussion Main Findingsmentioning
confidence: 99%
“…This finding further supports systematic reviews that have reported inconsistent and inconclusive effectiveness of physical treatments in tension-type headache aimed at mobilization. 14, 24,26 Considering these results and reported risks of cervical high-velocity thrust mobilization techniques, 1 clinicians should reconsider the use of these techniques in participants with CTTH.…”
Section: Discussion Main Findingsmentioning
confidence: 99%
“…2,3 Both episodic tension-type headache (ETTH) and chronic tension-type headache (CTTH) have important repercussions on the quality of life, affecting the working and social spheres, as well as the activities of daily living. 4 As for the treatments administered, Lenssinck et al 2 carried out a systematic review to assess the effectiveness of physiotherapy and spinal manipulation in the treatment of TTH and showed that there was no conclusive evidence of its effectiveness.…”
Section: Introductionmentioning
confidence: 99%
“…Chiropractic and spinal manipulation, for example, is often used for various pain syndromes, despite some literature reviews that fail to show any benefit over sham procedures and also show the potential for harm. 4,5 Another heavily investigated therapy is acupuncture, which is generally considered more invasive and carries with it the potential for adverse events.…”
Section: Résumémentioning
confidence: 99%